Dampak buku ajar IPA terpadu bermuatan literasi saintifik tema kesehatan pencernaan dalam model pembelajaran kontekstual adaptif pada hasil belajar siswa kelas VIII SMPN 7 Padang - Nofisatul Hayati; asrizal asrizal; Renol Afrizon (Universitas Negeri Padang, 2019)
The 2013 curriculum emphasizes the improvement and balance between soft skills and hard skills. Curriculum development is done to answer the challenges of the 21st century. The Indonesian government seeks to improve student learning outcomes by developing school literacy and science learning in an integrated manner in junior high school. The real conditions in schools show that teachers still have difficulty in implementing integration between Physics, Biology and Chemistry in the learning process. This can be seen from the low student learning outcomes. One solution to this problem is to apply the Integrated Science teaching book with scientific literacy themes to digestive health in adaptive contextual learning. The purpose of this study was to investigate the impact of integrated science teaching books with scientific literacy on the theme of digestive health in an adaptive contextual learning model on the learning outcomes of class VIII students of SMP 7 Padang. Type of this research is a quasi experiment with Randomized Control-Group Only Design. The population of this study was all eighth grade students at Padang 7 Junior High School with a sampling technique using purposive sampling and cluster random sampling. The research instruments consisted of observation sheets for attitude aspects, written tests for knowledge aspects and performance assessment sheets for skills aspects. The data obtained were analyzed using descriptive statistics and two average comparison tests. The results of the hypothesis indicate that there are differences in learning outcomes of students who use integrated science teaching books with scientific literacy on the theme of digestive health with students who do not use it. Student learning outcomes can be assessed in three aspects of learning. The three aspects are aspects of knowledge, aspects of attitude and aspects of skills. This indicates that the use of integrated science teaching books with scientific literacy on the theme of digestive health in an adaptive contextual learning model has a significant impact on student learning outcomes.